Pertumbuhan Dan Hasil Jagung Manis (Zea mays saccharata Sturt.) Pada Berbagai Dosis Dan Waktu Pemberian Pupuk Kandang Sapi - Ardaniah, Ardaniah (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2016)
Sweat corn is a vegatable that contains carbohydrates, protein, vitamine and sugar content levels are relatively high but low axunge content. In an effort to develop sweat corn often encountered obstacles basically fertility problem and low soil productivity. This research intead to analyze the effect of interaction and single factor dose cow manure and fertilization time on growth and yield of sweat corn. Research carried in integrated land STIPER Muhammadiyah Tanah Grogot, Tapis village sub-districts Tana Paser, district Paser since July-October 2015. This environtment design of this research groop random design (RAK) and the treatment design is split plot design. There are nine combinations of treatments are repeated three times. There are 27 total plots experiment. The result showed that interaction treatment give a significant influence for cob weight with husk and without husk and single treatment dose of cow manure 10 ton ha-1 and fertilizing at the same time planting has been able to increase growth and sweat corn crop yield.Keyword: manure, sweat corn, dose, time